Strategies to Build a Pesantren Culture Without Bullying: Implementation of Anti-Kekerasan Programs - setyowati, fina fitriawahyu; Dartim, Dartim (Institut Agama Islam An-Nawawi Purworejo, 2025)
Bullying and violence are serious problems that can occur in various environments, including in religious educational institutions such as Islamic boarding schools. As an institution that plays a role in shaping the character of students with high religious and moral values, boarding schools face challenges in creating an environment that is safe and free from bullying. This study aims to analyze the strategies applied in building a pesantren culture without bullying and evaluate the implementation of the anti-violence program at Al-Muayyad Islamic Boarding School in Surakarta. This research uses a field-based qualitative method (field research) with a case study approach. Data were obtained through primary and secondary sources, and collected through observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that Al-Muayyad Islamic Boarding School has implemented a comprehensive anti-bullying strategy through the formation of the Sarungan Team, which plays a role in preventing and handling cases of bullying and violence in the pesantren environment. This program has a positive impact, such as a decrease in the number of santri mutations and an increased sense of security and comfort in the pesantren environment. However, the implementation of this program still faces several obstacles, such as limitations in supervising students, a limited number of cadres, and challenges in deliberating with parents in certain cases. This research is expected to be a reference for religious education institutions in developing effective strategies to create a safe, comfortable, and free from bullying and violence pesantren environment.